ANALYSIS OF THE SITUATION IN PHOTOVOLTAIC CELLS ON THE NATIONAL AND INTERNATIONAL MARKET - Tirshu M.; Uzun M. (Problems of the Regional Energetics)
The paper is aimed to analyses of existing photovoltaic cells, its parameters, considering lifetime, efficiency and price. It was established, that efficiency of PV cells is situated in range of 5-30 percents. The PV cells with high efficiency (more than 20%) have a cost in 5-10 times more than PV cells with efficiency up to 15%. On the market of Republic Moldova are commercialized PV cells with efficiency up to 15% only. The lifetime of PV cells are situated between 20 and 30 years and after 15 years of life service its efficiency decreasing on about 10%. Additional, efficiency of PV cells depends also from temperature of environment and decreasing on 0,3% on each degree. It technical parameters a given at temperature of 25oC of environment. At the same time, it can be underlined, that in near future the development of PV cells will be aimed to using of organic cells which now have efficiency about 5-7%. In order to develop a new generation of PV cells more usefully it can be considered design, where nanocristal silicon layer is infed between thin layers of amorphous silicon. It offer a very high efficiency of PV battery, and more, it is possible to exclude bulkiness intermediate layers from silicon monocrystal and as a result the material cost decreasing.